Changing trends of incidence and prognosis of thyroid carcinoma - Farahati, Jamshid; Mäder, Uwe; Gilman, Elena; Görges, Rainer; Maric, Ines; Binse, Ina; Hänscheid, Heribert; Herrmann, Ken; Buck, Andreas; Bockisch, Andreas (Nuklearmedizin - NuclearMedicine, 2019)
Aim to evaluate the time trend of epidemiology of follicular cell derived thyroid cancer (TC) based on data from a well documented cancer registry.Methods Population based data on TC from Lower Franconia (LF), Germany, within 1981 and 2015 were analysed to estimate the regional epidemiology of TC. The incidence was assessed in 5-year-intervals for gender, histology, and tumor stage.Results Incidence of TC solely attributable to papillary TC (PTC) doubled mainly in T1- and T2-stages within the evaluation period from 4.5 to 8.7/100.000/y in females and 1.7 to 4.1/100.000/y in males. There was no significant change of follicular TC (FTC), whereas anaplastic TC (ATC) decreased in the same interval. The number of lymph-node metastases and T3-cases increased, while the frequency of T4-stage and distant metastases decreased. Increased incidences of T1- and T2-stages suggest an over-diagnosis. In contrast, increasing number of tumors at T3-stage and with lymph node involvement contradict the over-diagnosis as the only reason for rising incidence. Declining of T4-stages in spite of increasing of T3-stages and N1-cases indicates the value of timely detection and treatment of TC. In accordance, reduced incidence of advanced cancers with M1-stage and ATC cases promote our current management of TC.Conclusion Timely diagnosis and adequate risk-adopted treatment of thyroid cancer reduce the frequency of high-risk cases with distant metastases and the possible protracted dedifferentiation of TC to anaplastic features. Our analyses support the management algorithm in thyroid cancer according to the recent guidelines of German Nuclear Medicine Society.
Keywords: Epidemiology; screening; over-screening; over-diagnosis; thyroid cancer; Incidence; I-131-therapy